Dysregulated myokines and signaling pathways in skeletal muscle dysfunction in a cigarette smoke–induced model of chronic obstructive pulmonary disease - Lijiao Zhang; Chunxiao Li; Jing Xiong; Chun Chang; Yongchang Sun (Frontiers in Physiology, 2022)
Skeletal muscle dysfunction is an important extrapulmonary comorbidity of chronic obstructive pulmonary disease (COPD). Muscle-derived cytokines (myokines) play important roles in skeletal muscle growth and function, but their contributions to skeletal muscle dysfunction in COPD have not been fully understood. In the current study, by using a well-established mouse model of COPD with skeletal muscle dysfunction, we found that the expressions of Fndc5 (fibronectin type III domain-containing protein 5, the precursor of irisin) and peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α) were decreased, while myostatin (Mstn), phosphorylated extracellular regulated kinase (p-Erk1/2), and p-Smad3 expressions were upregulated in skeletal muscles from cigarette smoke-exposed mice and in cigarette smoke extract (CSE)-stimulated C2C12 myotubes. Treatment with Smad3 or Erk1/2 inhibitors partially restored the expression of Fndc5 in CSE-stimulated C2C12 myotubes. Taken together, CSE exposure, by upregulation of p-Erk1/2, promoted the expression of Mstn, which further inhibited Fndc5 expression by the p-Smad3/PGC-1α pathway, revealing a novel regulating mechanism of myokines in the pathogenesis of skeletal muscle comorbidities of COPD.